Subclinical impairment of myocardial and endothelial functionality in very early psoriatic and rheumatoid arthritis patients: Association with vitamin D and inflammation. (April 2018) - Lo Gullo, Alberto; Rodríguez-Carrio, Javier; Aragona, Caterina Oriana; Dattilo, Giuseppe; Zito, Concetta; Suárez, Ana; Loddo, Saverio; Atteritano, Marco; Saitta, Antonino; Mandraffino, Giuseppe
Abstract: Background and aims: Cardiovascular (CV) morbidity is increased in inflammatory joint diseases (IJD), as rheumatoid (RA) and psoriatic arthritis (PsA). Whereas increased prevalence of subclinical atherosclerosis has been reported in these conditions, whether an early myocardial functionality is also impaired remains unknown. The aim of this study was to evaluate the myocardial functionality by speckle-tracking echocardiography (STE) in recent onset RA and PsA patients and its potential associations with the levels of circulating CD34 + cells, vitamin D, and with disease activity. Methods: STE was used to assess the myocardial functionality in patients with very early RA (n = 41) and PsA (n = 35) without traditional CV risk factors, and 58 matched healthy controls (HC). Global longitudinal and circumferential strain (GLS and GCS) was estimated. Pulse wave velocity (PWV) and carotid intima-media thickness (cIMT) were measured as surrogate markers of atherosclerosis. Circulating CD34 + counts were evaluated by flow cytometry and vitamin D levels were quantified by HPLC. Disease activity was assessed by Disease Activity Score-28 (DAS28). Results: RA patients exhibited impaired GLS and GCS (both p < 0.001) as compared to HC, GLS being also altered in PsA ( p = 0.020 vs . HC). DAS28 was correlated to GLS (r = 0.908, p < 0.001) and GCS (r = 0.868, p < 0.001) in RA, these findings being confirmed by multivariate regression analyses adjusted for confounders and Principal Component Analyses. GLS and GCS were impaired in PsA patients with high disease activity as compared to HC, and GLS was found to be a predictor of cIMT in this condition. On the other hand, vitamin D was negatively associated with cIMT in HC (r = −0.308, p = 0.026) but not in PsA or RA, although decreased levels were observed (both p < 0.001). Vitamin D was an independent predictor of decreased CD34 + levels in PsA and RA. CD34 + counts negatively correlated DAS28, GLS and GCS in RA. Conclusions: Subclinical myocardial dysfunction is observed in IJD patients with preserved left-ventricular function and without traditional CV risk factors. Subclinical myocardial dysfunction was found to be a very early event in IJD. Disease activity was the main predictor of myocardial strain impairment. Interestingly, myocardial function was altered and associated with cIMT also in PsA patients with high disease activity. Highlights: Subclinical myocardial dysfunction is found in very early rheumatoid arthritis (RA) and psoriatic arthritis (PsA). Inflammatory burden is associated with altered myocardial function in inflammatory joint diseases (IJD). Speckle-tracking echocardiography may be useful for CV risk stratification in IJD.